Integration of Customary Law and the Theory of Legal Pluralism of the Parties to a Bank Credit Agreement Based on the Principle of Balance - Meher, Montayana; Abdunayimova, Dinara (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This article discusses the urgency of integrating customary law into banking credit agreements in Indonesia for all parties based on the principle of balance.Purposes of the Research: This study aims to analyze the integration of customary law and the theory of legal pluralism of the parties in bank credit agreements based on the principle of balance.Methods of the Research: This research is normative legal research with a conceptual and legislative approach.Results of the Research: The integration of customary law into banking credit agreements in Indonesia, based on Article 1339 of the Civil Code, which recognizes fairness, customs, and laws as binding elements of an agreement. Customary law, which emphasizes the principles of collectivity, trust, and deliberation, provides a strong social foundation and local legitimacy in credit agreements. The legal pluralism approach with the principle of balance serves as a key strategy to accommodate customary law values and mechanisms within formal banking practices, thereby reducing normative conflicts and enhancing protection and justice for indigenous communities with limited access to formal law. The integration of customary law into credit agreements not only strengthens the pluralistic national legal system but also creates agreements that are fair, proportionate, and respect local wisdom, while simultaneously increasing social legitimacy and practical solutions in resolving credit issues within indigenous communities.